KONSTRUKSI EKOTEOLOGI DALAM PELESTARIAN HUTAN ADAT BAYAN DI LOMBOK UTARA NUSA TENGGARA BARAT - Zerin Amalina (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The preservation of the Bayan customary forest in North Lombok is sustained not only by ecological practices but also by an ecotheological construction rooted in the values of Islam Wetu Telu and local customary traditions. This construction shapes the community’s worldview that regards the forest as a sacred space, a source of life, and an integral part of the cosmic order that must be protected. This study aims to examine how these religious and customary values are constructed, institutionalized, and internalized within the community’s environmental practices. Employing a qualitative method with an interpretive ethnographic approach, data were collected through participant observation, in-depth interviews, and documentation studies, and analyzed using Peter L. Berger’s social construction theory. The findings indicate that ecotheological values are expressed through rituals, symbols, and ecological actions (externalization); institutionalized through awig-awig (customary law), local leadership structures, and forest zoning systems (objectivation); and internalized into a collective ecological consciousness that forms the community’s religious habitus (internalization). Together, these processes produce a strong and sustainable ecological ethic, positioning the customary forest not merely as an ecological asset but also as an expression of faith and cultural identity. In conclusion, the ecotheological construction of the Bayan community serves as a spiritual and social foundation for forest preservation, offering a locally rooted conservation model relevant to contemporary sustainable environmental development.